PENGARUH PENGGUNAAN ELEKTROLISER DENGAN VARIASI DIAMETER KAWAT TEMBAGA DAN VARIASI LARUTAN TERHADAP DAYA MESIN SEPEDA MOTOR HONDA SUPRA- X 125D TAHUN 2007 - Purnomo, Kurniawan Adi (Jurnal Nosel, 2014)
The purposes of the research are to: (1) know effect of electrolyzer application with varied diameters of copper wire on engine power of Honda Supra X 125D 2007 Motorcycle; (2) know effect of electrolyzer application with varied solutions on engine power of Honda Supra X 125D 2007 Motorcycle. (3) know interaction used varied of diameters copper wire and varied solutions on engine power of Honda Supra X 125D 2007 Motorcycle. The research used descriptive-quantitative method. Sample of the research was Honda Supra X 125D 2007 Motorcycle with machine number JB51E2015321. The research was performed in PT. MOTORCOURSE TECHNOLOGY (MOTOTECH) Yogyakarta and used dynamometer or Dynotest. Data is obtained from magnitudes of engine power with the addition of electrolyzer tube with varied diameters of copper wire and varied solutions. The data of research is listed on table and presented as graphic and then, it is analyzed. The results of the research indicated that (1) there were effects of electrolyzer application with varied diameters of copper wire on power engine of Honda Supra X 125D 2007 Motorcycle was found. Among copper wires with diameters of 1,5 mm, 2,5 mm, and 4,0 mm, it was found that copper wire with diameter of 1.5 mm produced best effect on improving engine power; (2) there were effects of electrolyzer application with varied solutions on engine power of Honda Supra X 125D 2007 Motorcycle. KOH and Na2SO4 were used as solutions, and the first solution had best effect on the improvement of engine power. (3) there were interaction used varied diameter of copper wire and varied solutions on engine power of Honda Supra X 125D 2007 Motorcycle. The biggest interaction to improve the engine power is used copper wire with diameter 1,5 mm and KOH solution. The engine power increased 1,74 % from standard machine condition.